Crafting a Common Patrimony out of the Trans-Appropriative Nature of Water Resources - Bon, Emmanuel (Water Nepal, 2003)
How does one grasp the complexity of water values and implement them in an effective and legitimate way? Since 1975, the French way of addressing action problems related to environmental quality has led to the formalisation of an innovative approach called ‘patrimonial strategies’. From a methodological point of view this approach marks a break with the utilitarian approach to economic theory and with the property rights paradigm. In as much as the actual quality of water resources is trans-appropriative, it goes beyond the concerns of public or private property. Empirical evidence suggests that a complex web of actors (both private or public, including domestic users, agriculturists, industrialists and government agencies) has a significant impact on the quality of water resources. While they have different patterns of interaction with respect to water resources, i.e. different visions, strategies and objectives (be the health care, irrigation, access to drinking water, environmental sustainability, etc.), they face a common problem: the overall degradation of water resource qualities. However, actors by virtue of their action on the resource, i.e. performance, are in a position to co-supply and co-demand a certain level of quality. Thus, they become potential negotiators of patrimonial contracts for quality. This paper examines the core concepts of the total quality of water resources, trans-appropriativity and common patrimony. The procedure of patrimonial audit, which consists of ‘identifying’ stakeholders and quality systems, ‘diagnosing’ problems, ‘prospecting’ scenarios and formulating ‘action proposals’ and the potentialities of a local common patrimony of general interest, is outlined.Water Nepal Vol.9-10, No.1-2, 2003, pp.379-390